Development of structured modules to improve the mathematical understanding of the circle concept in class VIII Mataram 17 junior high school. (February 2020) - Mahsup,; Anwar, Y S
Abstract: The purpose of this research is to produce a structured module product to improve the understanding of the concept of circles in class VIII Mataram 17 Junior High School. The development model used in the development of this learning module is Dick and Carey's model of development. The type of data on this development is quantitative and qualitative data. Data collected in the form of polls, interviews, and tests. While the data analysis using qualitative descriptive analysis techniques and descriptive statistical analysis. Based on the expert assessment that the validity of the module content is in the first category with a percentage turnover of 96.4%, and the validity of the learning design is in an outstanding category with a percentage turnover of 93%. The results of the small group trials on the students gave the module assessment in the excellent class with a percentage of 82.05%, while in the field trials, students give evaluation results on the modules are in a proper category with a rate of 80.85%. Results of analysis of pretest and Postes obtained price t count 21.415, T price of table 1.69, which means t count > T table (very significant). Thus learning by using modules can improve the understanding of the circle concept.